Impact of government size and corruption on economic growth - Baklouti, Nedra; Boujelbene, Younes (International Journal of Accounting and Economics Studies, 2016)
This paper examines the role of government in economic growth by extending the neoclassical production-function by incorporating two dimensions of government such as, the size and quality. The size is measured by general government final consumption expenditures. The quality of governance is measured by the index of perception of corruption which is being tested in 12 countries in the MENA region in the period between 1998 and 2011. Our empirical results indicate that when the public sector is "too big", economic growth is negatively affected and that the relationship between corruption and economic growth is significantly negative with the bad effects of this phenomenon that include a loss of revenue for the state in the benefit of the individual, the increased costs related to the conduct of the affairs of the state, an inefficient use of public spending and stifling economic growth in the region. We argued then, that investments in the capacity which strengthened governance are a priority for improving the growth of the countries examined.